Pengaruh Penambahan Pollard dan Bekatul dalam Pembuatan Silase Rumput Odot (Pennisetum purpureum, Cv.Mott) Terhadap Kecernaan dan Produksi Gas Secara In Vitro - Hartutik Hartutik; Alifia Imtinatul Fajri; Artharini Irsyammawati (Jurnal Nutrisi Ternak Tropis, 2018)
The purpose of this research was to evaluate pollard and rice bran in dwarf elephant grass silage (Pennisetum purpureum, cv. Mott) processing on in vitro digestibilty and gas production. The materials were dwarf elephant grass, pollard and rice bran as additives. The research was arranged in randomized block design with 4 treatments and 3 replication based on rumen liquid collection. The treatments were: dwarf elephant grass without additive (T0), dwarf elephant grass + 20% pollard (T1), dwarf elephant grass + 20% rice bran (T2), dwarf elephant grass + 10% pollard + 10% rice bran (T3). Collected data were analyzed by analysis of variance and continued with Duncan’s Multiple Range Test (DMRT). Variables measured were in vitro dry matter digestibility (DMD) and organic matter digestibility (OMD), cumulative gas production (GP) and degradability from GP residue. The result showed that the treatments didn’t significantly effect (P>0.05) on DMD and OMD but highly significant effect (P<0.01) on cumulative GP and degradability. It could be concluded that dwarf elephant grass + 20% pollard (T1) was the best treatment based on DMD (62.34%), OMD (68.18%) and supported by highly number of cumulative GP and degradability. Thus it was suggested to do further research on fiber composition and in vivo assay.